Thecal plate morphology, molecular phylogeny, and toxin analyses reveal two novel species of Alexandrium (Dinophyceae) and their potential for toxin production - NURSYAHIDA, ABDULLAH; Teng, Sing Tung; Afiqah Hamilton, Hanifah; Law, Ing Kuo; Tan, Toh Hii; Bernd, Krock; Thomas M., Harris; Satoshi, Nagai; Lim, Po Teen; Urban, Tillmann; Leaw, Chui Pin (Elsevier B.V., 2023)
This study describes two novel species of marine dinophytes in the genus Alexandrium. Morphological characteristics and phylogenetic analyses support the placement of the new taxa, herein designated as Alexandrium limii sp. nov. and A. ogatae sp. nov. Alexandrium limii, a species closely related to A. taylorii, is distinguished by having a shorter 2ʹ/4ʹ suture length, narrower plates 1ʹ and 6ʹʹ, with larger length: width ratios, and by the position of the ventral pore (Vp). Alexandrium ogatae is distinguishable with its metasert plate 1ʹ having almost parallel lateral margins, and by lacking a Vp. Production of paralytic shellfish toxins (PSTs), cycloimines, and goniodomins (GDs) in clonal cultures of A. ogatae, A. limii, and A. taylorii were examined analytically and the results showed that all strains contained GDs, with GDA as major variants (6–14 pg cell− 1 ) for all strains except the Japanese strain of A. limii, which exclusively had a desmethyl variant of GDA (1.4–7.3 pg cell− 1 ). None of the strains contained detectable levels of PSTs and cycloimines.